Allergen immunotherapy for the polyallergic patient. Issue 6 (December 2016) - Wahn, Ulrich
Abstract : Purpose of review: Currently, dramatic changes in allergy treatment can be observed in many countries: The availability of monocomponent products with pharmaceutical quality for sublingual immunotherapy is likely to have a strong impact on all immunotherapy practices and the specialty in general. The market for patient-named products with allergenic mixtures can be expected to shrink. Allergists are concerned about the possibility that single-source products for immunotherapy might be insufficient to serve the needs of all 'polyallergic' patients. Recent findings: The availability of molecular IgE-testing as a novel diagnostic tool will clarify that much of the previously perceived 'polyallergy' has to be interpreted as 'pseudo-polyallergy.' It can be predicted that the needs of the vast majority of polysensitizations will be met by the novel allergen components, which are marketing for subcutaneous immunotherapy and sublingual immunotherapy. In countries where compounding of 'patient-tailored allergen extracts' has been traditionally practiced, diagnostic and therapeutic procedures are currently being challenged. A recent survey (Allermix) in Europe suggests that allergists believe that the vast majority of polyallergic patients can be adequately treated with registered products without compounding. Compounding by allergists or allergen manufacturers will still be necessary for a limited number of patients with several independent allergies. Summary: It appears that a limited portfolio aligned to health authority recommendations will be sufficient to answer treatment habits of allergists even in polysensitized patients.